A coordenação pedagógica nas escolas estaduais paulistas: as resoluções recentes e a atuação cotidiana na gestão e organização escolar - Fernandes, Maria José da Silva [UNESP] (My University, 2011)
This article analyzes the pedagogical coordination work in public schools of the state of São Paulo within a context of educational reforms occurred between 1996 and 2010. The paper analyzes the main resolutions published by the Secretariate of Education regarding the functions performed by coordinating teachers, and discusses data obtained from empirical research conducted with three schools in inner cities of the state of São Paulo, specifically in the final years of elementary school and high-school. The analysis has enabled us to identify the implications of educational reforms on the functions of coordinating teachers. In addition, we have identified and interpreted the ways in which subjects are (re)adjusted in school management and organization.

Este artículo analiza el trabajo de la coordinación pedagógica en las escuelas estaduales de São Paulo, en el contexto de las reformas educacionales ocurridas entre 1996 y 2010. El trabajo analiza las principales resoluciones publicadas por la Secretaría de Educación relacionadas a la función del profesor coordinador (PC) y discute parte de los datos obtenidos en una encuesta empírica realizada en tres escuelas en los últimos años de la Enseñanza Fundamental y de la Enseñanza Media del interior de São Paulo. El análisis permitió reconocer las consecuencias de las reformas educacionales para la función, además de la identificación e interpretación de las formas de (re) ajuste de los sujetos presentados en el trabajo de gestión y organización escolar.

Este artigo analisa o trabalho da coordenação pedagógica nas escolas estaduais paulistas no contexto das reformas educacionais, entre 1996 e 2010. Analisamos as principais resoluções publicadas pela Secretaria da Educação sobre a função de professor coordenador (PC) e discutimos parte dos dados obtidos em pesquisa empírica de base qualitativa realizada em três escolas dos anos finais do ensino fundamental e do ensino médio do interior paulista. A análise nos permitiu reconhecer as implicações das reformas educacionais para a função, além da identificação e interpretação das formas de reajustamento dos sujeitos apresentadas no trabalho de gestão e organização escolar.
Pedagogical coordination in the schools of the state of São Paulo: recent resolutions and daily practice in school management and organization
La coordinación pedagógica en las escuelas estaduales de São Paulo: resoluciones recientes y actuación diaria en la gestyión y organización escolar
Keywords: Pedagogical coordination; Educational reforms; Regulations; Coping strategies; School management; Coordinación pedagógica; Reformas educacionales; Regulaciones; Estrategias de enfrentamiento; Gestión de la escuela; Cordenação pedagógica; Reformas educacionais; Regulações; Estratégias de enfrentamento; Gestão escolar